Structural basis for serotonergic regulation of neural circuits in the mouse olfactory bulb. Issue 2 (8th October 2014) - Suzuki, Yoshinori; Kiyokage, Emi; Sohn, Jaerin; Hioki, Hiroyuki; Toida, Kazunori
ABSTRACT Olfactory processing is well known to be regulated by centrifugal afferents from other brain regions, such as noradrenergic, acetylcholinergic, and serotonergic neurons. Serotonergic neurons widely innervate and regulate the functions of various brain regions. In the present study, we focused on serotonergic regulation of the olfactory bulb (OB), one of the most structurally and functionally well‐defined brain regions. Visualization of a single neuron among abundant and dense fibers is essential to characterize and understand neuronal circuits. We accomplished this visualization by successfully labeling and reconstructing serotonin (5‐hydroxytryptamine: 5‐HT) neurons by infection with sindbis and adeno‐associated virus into dorsal raphe nuclei (DRN) of mice. 5‐HT synapses were analyzed by correlative confocal laser microscopy and serial‐electron microscopy (EM) study. To further characterize 5‐HT neuronal and network function, we analyzed whether glutamate was released from 5‐HT synaptic terminals using immuno‐EM. Our results are the first visualizations of complete 5‐HT neurons and fibers projecting from DRN to the OB with bifurcations. We found that a single 5‐HT axon can form synaptic contacts to both type 1 and 2 periglomerular cells within a single glomerulus. Through immunolabeling, we also identified vesicular glutamate transporter 3 in 5‐HT neurons terminals, indicating possible glutamatergic transmission. Our present study strongly implicates the involvement of brain regions such as the DRN in regulation of the elaborate mechanisms of olfactory processing. We further provide a structure basis of the network for coordinating or linking olfactory encoding with other neural systems, with special attention to serotonergic regulation. J. Comp. Neurol. 523:262–280, 2015. © 2014 Wiley Periodicals, Inc.